2022
DOI: 10.3389/fmicb.2022.1067671
|View full text |Cite
|
Sign up to set email alerts
|

Screening of β -damascenone-producing strains in light-flavor Baijiu and its production optimization via response surface methodology

Abstract: As a C13-norisoprenoid aroma substance, β-damascenone is a highly important aromatic compound and an active constituent. The purpose of this study was to investigate the change law of β-damascenone during the light-flavor Baijiu brewing process, and screen the indigenous microbial strains that produce this compound and optimize fermentation parameters for improving β-damascenone production using a statistical approach. In this project, Wickerhamomyces anomalus YWB-1 exhibited the highest producing activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…According to the findings of Wadetwar et al [ 37 ], it was observed that the incubation of actinomycetes, which were isolated from the Nagpur area, for a fermentation duration of 7 days using an inoculum size of 10%, along with the presence of yeast extract at a concentration of 0.4% and malt extract at a concentration of 1.0%, increased antibiotic production. The effects of starting pH and incubation temperature were found to be non-significant in this screening experiment since the test was conducted in circumstances closely approximating the ideal values for both parameters [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of Wadetwar et al [ 37 ], it was observed that the incubation of actinomycetes, which were isolated from the Nagpur area, for a fermentation duration of 7 days using an inoculum size of 10%, along with the presence of yeast extract at a concentration of 0.4% and malt extract at a concentration of 1.0%, increased antibiotic production. The effects of starting pH and incubation temperature were found to be non-significant in this screening experiment since the test was conducted in circumstances closely approximating the ideal values for both parameters [ 38 ].…”
Section: Discussionmentioning
confidence: 99%